2021
DOI: 10.3390/ijms222011039
|View full text |Cite
|
Sign up to set email alerts
|

Key to Life: Physiological Role and Clinical Implications of Progesterone

Abstract: The most recent studies of progesterone research provide remarkable insights into the physiological role and clinical importance of this hormone. Although the name progesterone itself means “promoting gestation”, this steroid hormone is far more than a gestational agent. Progesterone is recognized as a key physiological component of not only the menstrual cycle and pregnancy but also as an essential steroidogenic precursor of other gonadal and non-gonadal hormones such as aldosterone, cortisol, estradiol, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 82 publications
0
38
0
7
Order By: Relevance
“…It has similarly been stated that reduced serum testosterone concentrations are linked with elevation of the occurrence of CVD in men 33 . Progesterone acts as a chief part in CV and central nervous systems and influences mammary gland growth 34 . Little linked and total jeopardies of evolving CVD is allied for most females who are using by combination estrogen-progestin oral contraceptives [35][36] .…”
Section: Resultsmentioning
confidence: 99%
“…It has similarly been stated that reduced serum testosterone concentrations are linked with elevation of the occurrence of CVD in men 33 . Progesterone acts as a chief part in CV and central nervous systems and influences mammary gland growth 34 . Little linked and total jeopardies of evolving CVD is allied for most females who are using by combination estrogen-progestin oral contraceptives [35][36] .…”
Section: Resultsmentioning
confidence: 99%
“…It blocks the proliferation of estrogen to increase uterus receptivity, triggers genes for endometrium permanence for the attaching embryo, and downregulates trophoblast invasion by stabilizing the activity of MMPs 57 . The progesterone‐induced blocking factor mediates progesterone's immunomodulatory effect and increases the production of Th2 cytokines along with declining natural killer cell degranulation 58 . Healthy pregnant women have significantly higher progesterone‐induced blocking factor than women with preterm labor or abortion risk.…”
Section: Role Of Progesteronementioning
confidence: 99%
“…57 The progesterone-induced blocking factor mediates progesterone's immunomodulatory effect and increases the production of Th2 cytokines along with declining natural killer cell degranulation. 58 Healthy pregnant women have significantly higher progesteroneinduced blocking factor than women with preterm labor or abortion risk.…”
Section: Role Of Prog E S Teronementioning
confidence: 99%
“…Progesterone is a critical physiological component in women that also mediates Tryp catabolism and the production of essential compounds from the oxidation pathway [ 82 ]. In particular, animal research showed that progesterone facilitates the reduction of L-kynurenine-induced cortical spreading depression by increasing brain levels of KYNA [ 80 ].…”
Section: Introductionmentioning
confidence: 99%